Jonisering som luftrenare. Mätstudie i laboratorium. - Persson, Elin; Makhoul, Sara; Tillo, Lina (My University, 2011)
Air ionization is an air cleaning technology used to additionally clean air from particles and gases in order to achieve good indoor air quality. The technology mimics nature´s own ability to purify air of particles, microorganisms, organics and odors. The report includes an experimental study of air ionization as air cleaning in ventilation plants. The experimental study is made in a laboratory with two experimental arrangements with the purpose of studying the removal efficiency of particles, gases and odors when using point ionization (spetsjonisering) and an ionization tube. Since humans spend most of their lives indoors, it is an important factor that particles, gases and odors are removed so that good indoor air quality can be achieved. The study is made in a filter rig and in a constructed chamber. The filter rig studies are made to see the effect of point ionization and its efficiency to increase the separation degree of air-filters. Trials in the filter rig are made with different settings to study what gives the point ionization its best effect. Best effect is achieved with long distance between the point ionization and the air-filter, low flow and with re-circulated air. Experiments are also made with two different materials of air-filter where the results show that a synthetic filter gives the point ionization better condition than with glass fibre filters. Overall, the experimental study of the air-filter rig shows no clear effect of point ionization. Experiments conducted in the chamber with 100 % re-circulated air show however on a marked improvement of the separation degree of air-filter when point ionization gets turned on. The experiment with point ionization shows that measurements made with a Dust Trak (particles ≤2.5 μm) gives the highest efficiency. The decay speed of particles in size of 0.3-0.5 μm reduces when using ionization tube in the chamber compared to when only using air-filter and point ionization. The experimental study in the filter rig with point ionization does not show big improvement compared with the study made in the chamber. This could be due to the fact that the point ionization´s aggregate supplies the point tassels with too little voltage in relations to the flows used in the filter rig. The experimental studies from both arrangements show however that re-circulated air has a positive effect when using point ionization.
Keywords: Building Futures; Byggnadsteknik; Building Futures; Building engineering